Pelaksanaan Pembelajaran Bahasa Inggris di Kelas 1B SDN 1 Pengadilan - Nur Faujiah, Yuni (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2025)
Every teacher must have not only fundamental teaching skills, but also other competencies. Simply completing educational activities is insufficient; you must reflect by self-evaluating, considering what to do as an educator, and maintaining the spirit of offering the best to pupils. The aimed to determine the results of reflection on English learning in elementary schools. The method used in this research is the qualitative method, which uses a narrative inquiry approach. The results of the study presented a reflection report conducted after teaching to analyze things that support and not, things that go well and things that still need to be improved, as well as solutions that are done. Reflecting on every lesson is essential for teachers and prospective teachers. By reflecting, we can find out the obstacles faced during learning. So that we can overcome this to be better in the future. As a result of this research, teachers will be able to understand better to the various situations that arise in the classroom and develop the ability to improve teaching standards to achieve the desired results